Bevacizumab: the first FDA-approved angiogenesis inhibitor in the treatment of non-small cell lung cancer - Evans, Tracey (Henry Stewart Talks, 2009)
Lung cancer incidence, Survival by treatment group, Selected trials of novel agents + chemotherapy, Bevacizumab, Vascular Endothelial Growth Factor (VEGF), Principles of angiogenesis, Bevacizumab in NSCLC: not for everybody, Randomized phase II trial of Paclitaxel/Carboplatin with/without Bevacizumab in NSCLC, Hemorrhagic events, Example of tumor cavitation in lung following treatment with chemotherapy and Bevacizumab, Patient haracteristics, Response rates, Hematologic and non-hematologic toxicity, Treatment related deaths, Efficacy by gender and age, NCCN pactice guidelines in oncology-v.2.2008, AVAiL: phase III trial of Bevacizumab + Gemcitabine and Cisplatin in advanced non|squamous cell NSCLC, Second line therapy for advanced NSCLC: the role of Bevacizumab, Adjuvant therapy in NSCLC, Can a broader range of patients be safely treated with Bevacizumab?, Protocol AVF3744g: BRIDGE trial, Bevacizumab in small cell lung cancer, Other VEGF inhibitors, Overall survival by histology, Toxicity of small molecular agents
Archived at 2021/02/25